2021
DOI: 10.13057/biodiv/d221248
|View full text |Cite
|
Sign up to set email alerts
|

The effects of introduction of the Sulawesi Endemic Stingless Bee Tetragonula cf. biroi from Sulawesi to Java on foraging behavior, natural enemies, and their productivity

Abstract: Abstract. Suhri AGMI, Soesilohadi RCH, Agus A, Kahono S. 2021. The effects of introduction of the Sulawesi Endemic Stingless Bee Tetragonula cf. biroi from Sulawesi to Java on foraging behavior, natural enemies, and their productivity. Biodiversitas 22: 5624-5632. The existence of species in an environment has gone through a long adaptation process to the natural environment. This study aims to determine the behavior of bees, pollen types, natural enemies, and products of the Sulawesi endemic bee Tetragonula c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…The field activity of bees exiting and entering after transferring the colonies to three different hive materials remained low, ranging from 34% to 51.76% compared to tree hallows. Similar results were observed [10], indicating that the field activity of T. biroi bees remained low at 39% in new hives after colony transfer during a three-month observation period. The low number of bees exiting and entering is likely due to the limited number of worker bees in the new colony.…”
Section: Activity Of Bees Entering and Exiting The Hivessupporting
confidence: 85%
“…The field activity of bees exiting and entering after transferring the colonies to three different hive materials remained low, ranging from 34% to 51.76% compared to tree hallows. Similar results were observed [10], indicating that the field activity of T. biroi bees remained low at 39% in new hives after colony transfer during a three-month observation period. The low number of bees exiting and entering is likely due to the limited number of worker bees in the new colony.…”
Section: Activity Of Bees Entering and Exiting The Hivessupporting
confidence: 85%
“…Stingless bees can adapt to environmental changes (temperature, humidity, and rainfall) and changes in food sources within a few weeks to 3 months to form perfect colonies [90]. The transfer of colonies of stingless bees between islands in Indonesia and from the highlands to the lowlands on the island of Sulawesi has caused many colony deaths, and the colonies did not produce well [91].…”
Section: Meliponiculture In Indonesiamentioning
confidence: 99%
“…However, Kahono et al (2018) reported that T. biroi is also found in Papua. Suhri et al (2021) reported that the foraging activity of T. biroi is significantly lower at the introduced habitat in Bantul, Purworejo, and Magelang (Java) than in Luwu and Bone (Sulawesi) which is impacts greatly decreased the honey production. The introduction of the T. biroi by the beekeepers in West Lombok, Indonesia, aims to obtain higher honey production and propolis to improve and increase their income.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, beekeepers usually select the stingless bee with high productivity and the process of beekeeping the stingless bee is called meliponiculture. For example, Tetragonula biroi (Friese, 1898) is mainly found on Sulawesi Island or called Sulawesi endemic stingless bee (Suhri et al 2021). However, Kahono et al (2018) reported that T. biroi is also found in Papua.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation